The Correlation between Cerebral Blood Flow Measured by Bedside Xenon-CT and Brain Chemistry Monitored by Microdialysis in the Acute Phase following Subarachnoid Hemorrhage - Rostami, Elham; Engquist, Henrik; Howells, Timothy; Ronne-Engström, Elisabeth; Nilsson, Pelle; Hillered, Lars Tomas; Lewén, Anders; Enblad, Per (Frontiers in Neurology, 2017)
Cerebral microdialysis (MD) may be used in patients suffering subarachnoid hemorrhage (SAH) to detect focal cerebral ischemia. The cerebral MD catheter is usually placed in the right frontal lobe and monitors the area surrounding the catheter. This generates the concern that a fall in cerebral blood flow (CBF) and ischemic events distant to the catheter may not be detected. We aimed to investigate if there is a difference in the association between the MD parameters and CBF measured around the microdialysis catheter compared to global cortical CBF and to CBF in the vascular territories following SAH in the early acute phase. Microdialysis catheter were placed in the right frontal lobe of 30 SAH patients and interstitial glucose, lactate, pyruvate, glycerol and lactate/pyruvate ratio were measured hourly. CBF measurements were performed during day 0-3 after SAH. Global cortical CBF correlated strongly with CBF around the microdialysis catheter (CBF-MD) (r = 0.911, p = <0.001). This was also the case for the anterior, middle and posterior vascular territories in the right hemisphere. A significant negative correlation was seen between lactate and CBF around the microdiaylsis catheter (CBF-MD) (r = -0.468, p = 0.009). The same relation was observed between lactate and CBF in anterior vascular territory but not in the middle and posterior vascular territories. In conclusion, global CBF 0-3 days after severe SAH correlated strongly with CBF-MD. High lactate was associated with low global CBF and low regional CBF in the right anterior vascular territory, when the MD catheter was placed in the right frontal lobe.